The effects of power posing on neuroendocrine levels and risk-taking - Efrat Barel; Shosh Shahrabani; Lila Mahagna; Refaat Massalha; Raul Colodner; Orna Tzischinsky (BMC Psychology)
Abstract Background The current study attempted to replicate the original findings regarding the effects of power posing on testosterone and cortisol levels, risk-taking behavior, and perceived power. We further extended the investigation by testing the effect of power posing on estradiol and progesterone levels. Methods A sample of 92 young adults (30 males; 32 females taking oral contraceptives; and 30 females not taking oral contraceptives who were in their midluteal phase) were randomly assigned to high-power-pose or low-power-pose conditions and asked about their feelings of power. They completed a risk-taking task, and their neuroendocrine levels were measured both at baseline and following the power manipulation. Results Power posing was not found to replicate the original results regarding effects on testosterone levels or feelings of power; however, our findings partially supported the original results regarding effects on cortisol levels and risk-taking. Among high-power posers, a decrease in cortisol levels was associated with risk tolerance. Power posing was not found to influence progesterone levels. However, among females taking oral contraceptives, high-power posing increased estradiol levels. Conclusions These preliminary findings suggest that estradiol is influenced by short-term exposure to social cues under specific hormonal profiles.